The podium illusion: a phenomenological study of the influence of social support on well-being and performance in elite para swimmers - Aitchison, B.; Rushton, A. B.; Martin, P.; Soundy, A.; Heneghan, N. R. (BMC Sports Science, Medicine and Rehabilitation, 2021)
Background: The value of social support in enhancing performance is well established in non-impaired and sub-international level athletes with impairments. Despite this, no research to date has explored the experiences of social support in elite para-athletes. The aim of this study was to explore the experiences of social support in elite British para-swimmers and the influence on their wellbeing and performance. Methods: A hermeneutic phenomenological study involving semi-structured interviews was undertaken with 8 elite British para-swimmers (3 male, 5 female, mean age 24.9 years). Participants represented 5 para-swimming classes and all 10 of the International Paralympic Committee impairment categories. Data were analysed following a modified version of the Framework Method. Research quality and trustworthiness were ensured through employing techniques including data triangulation, member checking and reflexivity. Results: Five themes and 11 sub-themes were generated. The five themes were: `the coach-athlete relationship`, `team bond`, `tangible aid`, `The Podium Illusion` and `British para-swimming`. The overall findings and the magnitude of support mentioned in the fourth theme led to the development of a new model called `The Podium Illusion` which reflects the magnitude of support that is available to elite para-swimmers to help maximise their performance and wellbeing. Conclusion: Social support is essential for athlete wellbeing and performance. Findings underpin a new model, `The Podium Illusion`.